An introduction to atmospheric gravity waves - Nappo, C. J. (International geophysics series ;, 2013)
Gravity waves exist in all types of geophysical fluids, such as lakes, oceans, and atmospheres. They play an important role in redistributing energy at disturbances, such as mountains or seamounts and they are routinely studied in meteorology and oceanography, particularly simulation models, atmospheric weather models, turbulence, air pollution, and climate research. An Introduction to Atmospheric Gravity Waves provides readers with a working background of the fundamental physics and mathematics of gravity waves, and introduces a wide variety of applications and numerous recent advances. Nappo provides a concise volume on gravity waves with a lucid discussion of current observational techniques and instrumentation. An accompanying website contains real data, computer codes for data analysis, and linear gravity wave models to further enhance the reader's understanding of the book's material. Companion web site features animations and streaming video Foreword by George Chimonas, a renowned expert on the interactions of gravity waves with turbulenceIncludes a new application-based component for use in climate and weather predictions.- Resumé vydavatel